Networks of trade in raw materials and technological innovations in prehistory and protohistory : an archaeometry approach : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). - Delfino, Davide, 1976-; Piccardo, Paolo,; Baptista, João Carlos, (Archaeopress archaeology., 2016)
The papers collected in this book correspond to the lectures held during session B34 of UISPP conference in Burgos (June 2014) where the presentation of multidisciplinary works were encouraged. The main goal of bringing together specialists from various disciplines (humanities and natural sciences) was to debate, from different perspectives, the networks in raw materials and technological innovation in prehistory and protohistory, involving investigation topics typical of archaeometry: archeometallurgy, petrography, and mineralogy.